Perbedaan Hasil Belajar Fisika Melalui Model Pembelajaran Kooperatif Tipe Numbered Heads Together (NHT) Berbantuan Kartu Soal dengan Model Pembelajaran Direct Instruction Di SMAN 7 Mataram Tahun Ajaran 2015/2016 - Febri Susanti; Syahrial Ayub; Muhammad Taufik (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2016)
This research is aimed to know the difference between physics learning result through numbered heads together type cooperative learning model helped by question card and physics learning result through direct instruction learning model at SMAN 7 Mataram on academic year of 2015/2016. This research was an experimental study with pretest posttest control group design. The population in this research was all the students of XI IPA SMAN 7 Mataram. Based on sampling process using cluster random sampling tehnique, XI IPA 7 was choosen as the experiment A class and XI IPA 6 was choosen as the experiment B class. The result of the test analized using t-test polled varians showed that tcount was 5,98 and ttable was 1,99 in the significant level ofÃÂ 5 % with the degree of freedom (df) of 61. Since tcount > ttable, Ho was rejected and Ha was accepted. It can be concluded that there were a difference between physics learning result through numbered heads together type cooperative learning model helped by question card and physics learning result through direct instruction learning model at SMAN 7 Mataram on academic year of 2015/2016